2018
DOI: 10.1016/j.biopsych.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Relationship Between Interstitial Fluid–Cerebrospinal Fluid Exchange, Amyloid-β, and Sleep

Abstract: Amyloid-β (Aβ) plaques are a key histopathological hallmark of Alzheimer's disease (AD), and soluble Aβ species are believed to play an important role in the clinical development of this disease. Emerging biomarker data demonstrate that Aβ plaque deposition begins decades before the onset of clinical symptoms, suggesting that understanding the biological determinants of the earliest steps in the development of AD pathology may provide key opportunities for AD treatment and prevention. Although a clinical assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 117 publications
0
94
0
2
Order By: Relevance
“…The clearance of amyloid from the brain during sleep is primarily via the glymphatic pathway [66,67]. These lymphatic vessels exit the cranium along veins and arteries associated with the middle meningeal arteries, transporting waste via the deep cervical lymph nodes to the systemic circulation (reviewed in [68]).…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…The clearance of amyloid from the brain during sleep is primarily via the glymphatic pathway [66,67]. These lymphatic vessels exit the cranium along veins and arteries associated with the middle meningeal arteries, transporting waste via the deep cervical lymph nodes to the systemic circulation (reviewed in [68]).…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…The glymphatic activity seemed to be an important feature of the sleeping brain, rather than of the awake brain. Therefore, these changes in the paravascular flow could underlie the circadian fluctuations in extracellular and CSF Aβ levels observed in both rodents and humans [129]. In a study comparing awake mice with mice in states of physiological sleep or sleep induced by anesthesia, Xie and colleagues [130] found that Aβ was eliminated more efficiently (at twice the speed) during physiological sleep or anesthesia, than during wakefulness.…”
Section: Sleep and Glymphatic Systemmentioning
confidence: 99%
“…Based on these results, many researchers are focusing their attention on this novel mechanism linking sleep, metabolite clearance and the development of AD [127,129,[132][133][134], even though it has received contrary and critical opinions [135].…”
Section: Sleep and Glymphatic Systemmentioning
confidence: 99%
“…However, it is mostly unknown how the CSF, directly or indirectly, supplies the brain parenchyma with the interstitial fluid (ISF), the required “internal milieu.” There are different and sometimes conflicting data concerning the interactions of the two fluid systems (Abbott, ; Abbott, ; Boespflug & Iliff, ; Brinker, Stopa, Morrison, & Klinge, ; Hladky & Barrand, ; Klarica, Radoš, & Orešković, ; Ma et al, ; Nakada & Kwee, ; Orešković, Radoš, & Klarica, ; Redzic, ). Whether the CSF through diffusion and/or convection may enter into the interstitial space of the neural parenchyma from the ventricular space through the ependymal lining and/or through the perivascular spaces of the larger vessels, are still under question (Boespflug & Iliff, ; Hladky & Barrand, ; Klarica et al, ). It is also not clear whether the CSF/ISF can flow within the very dense neuronal parenchyma or it is only diffusion that drives the fluid exchange (Abbott, ; Abbott, ).…”
Section: Introductionmentioning
confidence: 99%